Improving the Utilization of Diets Low in Crude Protein for Broiler Chicken 1. Evaluation of Special Amino Acid Supplementation to Diets Low in Crude Protein - Jiang, Q.; Waldroup, P.W.; Fritts, C.A. (International Journal of Poultry Science, 2005)
Reduction of the dietary crude protein (CP) by amino acid supplementation is effective to a point but performance eventually declines. This study was conducted to determine if supplementation with certain amino acids that serve as precursors to metabolites involved in the urea cycle or the formation of essential amino acids might improve the performance at low protein levels. Diets were formulated to meet 100% or 110% of NRC recommendations for essential amino acids with Lys at 110% or 120% of recommendations. The CP levels were 16, 18, 20, 22 or 24%. The CP and ME equivalency values of amino acids were considered in the formulation. A minimum dietary electrolyte balance [(Na+K)-Cl)] of 200 meq/kg was maintained. Amino acids added to the low CP diets included: 1) Gly; 2) Gly + Arg; 3) Gly + Pro; 4) Arg + Pro; 5) Gly + Arg + Pro; 6) Gly + Arg + Pro + Glu. The Gly, Arg, and Pro were added at 0.2% while Glu was added at 0.4%. Each dietary treatment was fed to six pens of five male chicks from 1 to 21 d. Feeding diets with less than 22% CP resulted in loss in the body weight (BW) and impaired the feed conversion ratio (FCR) regardless of the amino acid status. Supplementation of low CP diets with Gly significantly improved the performance of broilers but did not reach that obtained on diets with 22 or 24% CP. None of the other amino acid supplements consistently influenced the performance of chicks in the absence of Gly. These data suggest that Gly may be a limiting factor in diets low in CP. It is likely that some of the requirements for lesser researched essential amino acids may be insufficient to support performance at lower levels of crude protein.